Rational use of blood calcium determinations - Ferreira-Junior, Mario; Lichtenstein, Arnaldo; Sales, Maria Mirtes; Taniguchi, Leandro Utino; Aguiar, Francisco José Bueno de; Fonseca, Luiz Augusto Marcondes; Sumita, Nairo Massakazu; Duarte, Alberto José da Silva (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: This study was motivated by the recent excessive increase in requests for blood calcium determinations and laboratory tests in general, in the Hospital das Clínicas complex of Faculdade de Medicina, Universidade de São Paulo (HCFMUSP). Its aim was to suggest rules for the determination of total and ionized calcium in our intensive care units, emergency department, wards and outpatient services, thus contributing towards improving the quality of medical care and achieving more appropriate use of human and financial resources. DESIGN AND SETTING: Critical analysis on clinical and laboratory data and the pertinent scientific literature, conducted by the study group for rational clinical laboratory use, which is part of the Central Laboratory Division, HCFMUSP. METHODS: The study group reviewed scientific publications, statistics and clinical and laboratory data concerning requests for total and ionized calcium determinations in the settings of intensive care units, emergency department, wards and outpatient services. RESULTS: From this critical analysis, clinical decision flow diagrams aimed at providing guidance for ordering these tests were constructed. CONCLUSIONS: Use of the proposed flow diagrams may help to limit the numbers of inappropriate requests for ionized and total calcium determinations, with consequent reductions in the number of tests, risks to patients and unnecessary costs.